Novel ZAP-70-Related Immunodeficiency Presenting with Epstein–Barr Virus Lymphoproliferative Disorder and Hemophagocytic Lymphohistiocytosis - Moriah Forster; Timothy Moran; Anne Beaven; Timothy Voorhees (Case Reports in Immunology)
Zeta-chain-associated protein kinase 70 (ZAP-70) plays an integral role in the T-cell antigenic receptor complex. A deficiency of this kinase leads to a phenotype of severe combined immunodeficiency, while hypomorphic mutations of the kinase lead to more mild immunodeficiency phenotypes. We present a case of a 21-year-old patient with lymphadenopathy who was found to have Epstein–Barr virus (EBV) lymphoproliferative disease (LPD) and the development of hemophagocytic lymphohistiocytosis (HLH). On further workup, the patient was ultimately found to have a homozygous intrionic mutation in ZAP-70. This is a novel ZAP-70 mutation (c.1623 + 5G > A) associated with combined immunodeficiency and an EBV-positive LPD. A primary immunodeficiency is important to consider in a young, otherwise healthy patient presenting with an EBV-positive LPD.